2016
DOI: 10.1371/journal.pone.0167146
|View full text |Cite
|
Sign up to set email alerts
|

Choice of High-Dose Intravenous Iron Preparation Determines Hypophosphatemia Risk

Abstract: BackgroundFerric carboxymaltose (FCM) and iron isomaltoside 1000 (IIM) are increasingly used because they allow correction of severe iron deficiency in a single infusion. A transient decrease in serum phosphate concentrations is a frequent side effect of FCM.AimTo characterize this adverse event and search for its predictors in a gastroenterology clinic patient cohort.MethodsElectronic medical records of patients attending the University Hospital of Innsbruck were searched for the keywords ferric carboxymaltos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
(14 reference statements)
2
50
0
4
Order By: Relevance
“…Hypophosphatemia after ferricarboxymaltose is usually transient and reversible, although rarely, severe cases have been reported after repeated infusions. 96 Minor/moderate infusion reactions (nausea, pruritus, urticaria, flushing, back or thoracic pain), often self-limited, may be observed in 1:200 infusions and more serious reactions (hypotension, dyspnea) in 1:200 000. 95 Although globally IV treatment seems safe, the number of reported patients is usually too limited to detect extremely rare anaphylactic reactions, such as those once caused by high molecular weight iron dextran.…”
Section: Ironmentioning
confidence: 99%
“…Hypophosphatemia after ferricarboxymaltose is usually transient and reversible, although rarely, severe cases have been reported after repeated infusions. 96 Minor/moderate infusion reactions (nausea, pruritus, urticaria, flushing, back or thoracic pain), often self-limited, may be observed in 1:200 infusions and more serious reactions (hypotension, dyspnea) in 1:200 000. 95 Although globally IV treatment seems safe, the number of reported patients is usually too limited to detect extremely rare anaphylactic reactions, such as those once caused by high molecular weight iron dextran.…”
Section: Ironmentioning
confidence: 99%
“…In a study of women with a history of heavy uterine bleeding, serum phosphate fell below 0.65 mmol/L in 10 of 25 patients who received FCM compared to none of the 30 women who received iron dextran . In a retrospective study, hypophosphatemia (<0.8 mmol/L) was noted more commonly in the 55 patients who received FCM (45.5%) than in the 26 who received iron isomaltoside (4%) . In a prospective RCT, hypophosphatemia (<0.6 mmol/L) also occurred in 0.4% of 997 patients administered ferumoxytol and 38.7% of 1000 who received FCM .…”
Section: Discussionmentioning
confidence: 93%
“…Even mild hypophosphatemia can contribute to osteomalacia over time . A retrospective study showed that hypophosphatemia lasted for ≥2 months in 13 of 17 patients treated with a single dose of FCM, suggesting a persistent hypophosphatemic effect …”
Section: Discussionmentioning
confidence: 99%